Synthesis, characterization and biological activities of hydrazone schiff base and its novel metals complexes - Hussain, Iqbal; Ullah, Aaqib; Ullah Khan, Atta; Ullah Khan, Wali; Ullah, Riaz; A. Naser, Abdelaaty A. Shahat Almoqbil; Mahmood, Hafiz Majid (Penerbit Universiti Kebangsaan Malaysia, 2019)
Recently, researchers are focusing on the synthesis of Schiff base complexes due to their promising biological activities and frequent use in the pharmaceuticals. In the present study we synthesized Schiff base of salicyldehyde and 2, 4-dinitrophenylhydrazine by modified method and its novel metal complexes with Cu (II), Zn (II), Co (II), Ni (II), Mn (II), V (II) and AU (IIII). For spectroscopic studies and characterization, UV-Vis and FT-IR spectroscopy were used. The Schiff base and its metals complexes were tested for antimicrobial, cytotoxic and antioxidant activities. Significant results are showed by the all synthesized complexes.